New Strategies in Applied Linguistic Research for Health Therapy - Siregar, Iskandarsyah (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
The study "New Strategies in Applied Linguistic Research for Health Therapy" explores the critical role of linguistic strategies in enhancing therapeutic outcomes and improving patient communication within healthcare settings. By integrating qualitative and quantitative methods, the research highlights the effectiveness of metaphorical language, politeness strategies, and the strategic use of narratives in fostering patient engagement, satisfaction, and treatment adherence. The metaphorical language was found to bridge the gap between complex medical jargon and patient understanding, while politeness and empathy were essential in building strong therapeutic relationships. Using narratives gave patients a coherent framework to understand their health journeys, particularly in managing chronic conditions. Training healthcare professionals in these linguistic strategies could significantly enhance patient-centred care. The study underscores the importance of applied linguistics in health care and calls for further research and integration of these strategies into clinical practice to optimize health outcomes.